Encyclopedia of Pain - Gebhart, Gerald F.; Schmidt, Robert F. (Springer Berlin Heidelberg : Imprint: Springer, 2013)
This is the most comprehensive overview available anywhere on the broad, multi-faceted and complex topic of pain Ớ<U+001c> and the rapidly evolving scientific and medical disciplines that seek to understand, assess and treat pain. The second edition of the℗ Encyclopedia of Pain is fully updated and℗ has been expanded by over 100 new essays.It includes more than 3,000 entries and provides clear, detailed and up-to-date coverage of the current state of research, and treatment of pain. In addition, detailed essays provide in-depth information on all aspects of nociception and pain, including substrates, causes, pathophysiology, symptoms and signs, diagnoses and treatment. More than 600 color figures enhance understanding of this too-little-understood topic. Solidly structured and inclusive, this reference is an invaluable tool for clinical scientists and practitioners in academia, health care and industry, as well as students, teachers and interested laypersons.